A Review on Treatment of Alzheimer’s Disease in Traditional Medicine Vs. Modern Science - Ms. Rashda Khatoon Shaikh; Dr. (Mrs). Vanita G. Kanase (International Journal of Pharma and Bio Sciences, 2022)
Alzheimer’s is a degenerative brain disease associated with memory depletion and mild cognitive dysfunction, leading to dementia. Medicinal plants have a major role to play in Alzheimer’s and memory loss control. Ayurveda, homeopathy, Siddha and Unani medicine systems are main conventional therapeutic approaches. Herbal remedies, like that of the Egyptians, Chinese and Indians have their roots in ancient times. Use of medicinal herbs in of AD treatment includes improving overall health and well-being. Interest in medicinal herbs has grown fast during the recent years leading to increased interest of researchers in therapeutic utilization plants for treatment and enhancement of disease and wellbeing, often without severe side effects. The modern age of drug discovery in Alzheimer’s disease began with the proposal of the cholinergic memory impairment hypothesis and the 1984 research criteria for AD. There are modest symptom-reducing effects of FDA authorized medications, but they really does not affect the eventual course of the AD. In the campaign against Alzheimer’s disease, the hunt for newer drugs which are safe and effective are already required the cooperation of large number of researchers with many willing subjects. But that’s a long way off! 146 medications have been rejected since 1998. Popular herbal plants for treating Alzheimer’s disease are discussed in this review. The report also centered on FDA-approved medications for treating Alzheimer’s disease. This review discusses all aspects of AD treatment including the comparison between the traditional and the Allopathic medicines that was missed by some articles. Most review studies focus on either traditional treatment or the management in Modern science of the disease but rarely on a comparison of both. The study also addresses the possibilities for the management of AD in future.